Effects of High-Frequency Electromagnetic Field on Ghrelin`S Quantitative Changes and Animal Memory - Dondoladze, Khatuna; Nikolaishvili, Marine; Zurabashvili, David (European Scientific Journal, ESJ, 2016)
Ghrelin is one of the major ways of improving memory, which is approved by different amino acids ratio. However, reducing the concentration of Ghrelin helps to prevent the implementation of generated and stiffened nutritional act. The processes of stimulation cause various improvement of expressed behavior on positive stimulus. This is based on the type of overpass labyrinth for improving the reflexive behavior to two feeding test. These facts approve that the processes which was developed as a result of Ghrelin`s and EMF action and the central mechanisms of animals behavioral reaction on positive stimulus were connected to each other by morphofunctional and neurochemical organization.